2002
DOI: 10.1111/j.1749-6632.2002.tb04503.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of the Serine Protease Inhibitor Neuroserpin in Endocrine Cells

Abstract: Serine proteases play essential roles in a wide variety of cellular processes in endocrine cells. There is a growing interest in the roles of serine protease inhibitors, or serpins, as key regulators of their activity. We have cloned two neuroserpin cDNAs from a rat pituitary cDNA library and confirmed tissue plasminogen activator as a potential target for this inhibitor. We show that neuroserpin transcripts are expressed by endocrine cells in the adrenal and pituitary glands and that immunoreactive neuroserpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Neuroserpin may alter cell survival and intercellular communication in mature endocrine tissues by regulating cell adhesion. 23 These findings support the hypothesis that neuroserpin may also cause an outgrowth response of prostate cancer cells and promote the migration of cancer cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Neuroserpin may alter cell survival and intercellular communication in mature endocrine tissues by regulating cell adhesion. 23 These findings support the hypothesis that neuroserpin may also cause an outgrowth response of prostate cancer cells and promote the migration of cancer cells.…”
Section: Discussionsupporting
confidence: 79%
“…23 The extension of cellular processes by endocrine cells may aid in the migration of cells to their final location in the developing gland. Neuroserpin may alter cell survival and intercellular communication in mature endocrine tissues by regulating cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that serine proteases play an essential role in hormone biosynthesis in endocrine organs (Hill et al 2002). Our data show that expression of several serine protease inhibitors in adrenals is suppressed by LXR agonist treatment including Spil-1, -3 and -4 (Figs 5 and 6).…”
Section: Discussionmentioning
confidence: 52%
“…Also in PC12 and AtT20 cell lines transfected with neuroserpin, the protein was localized in secretory granules [31]. Proposed functions of neuroserpin in the pituitary include the regulation of intragranular proteases and, following regulated secretion, inhibition of enzymes regulating cell-extracellular matrix interactions [29]. On the basis of results from studies on Drosophila Spn4.1, Osterwalder et al [18] also suggested that neuroserpin, the closest vertebrate Spn4.1 orthologue, might function intracellularly as a regulator of prohormone processing.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroserpin represents a recently identified serpin family member, which is expressed primarily in neuronal and neuroendocrine tissues. Thus far, several roles for neuroserpin have been proposed, among which an involvement in neuronal plasticity and learning [10], neuronal cell survival [12], neurite outgrowth, and intercellular communication in mature neuroendocrine tissues by the regulation of cell adhesion [29]. …”
Section: Discussionmentioning
confidence: 99%